Professional standards, competence and capability. Issue 1 (11th February 2014) - Lester, Stan
Abstract : Purpose: – The purpose of this paper is to examine whether the idea of competence in its various forms provides a sufficient basis for developing standards of professional practice. Design/methodology/approach: – Three existing studies of professional standards and qualifying processes are drawn upon, carried out by the author in 2007, 2009 and 2012. Findings: – Professional standards frameworks are informed by several different approaches to competence, although an external or activity-based approach – similar in principle to that used in UK occupational standards – predominates. However, there are limits to the extent to which a competence-based approach can adequately represent complex professional work, and there is scope to improve the relevance and robustness of frameworks through introducing the idea of capability. Evidence is presented to show that this is beginning to occur in some of the better-designed recent frameworks. Practical implications: – Using the idea of capability in professional standards is likely to have two implications. One is that standards focus at a high level on the work of the profession rather than on specific job roles, and the other is that pervasive themes such as ethics, judgement and professionalism are written into the standards in a way that ensures they apply across the breadth of practice rather than become treated as separate topics or areas of competence. Originality/value –: Professional standards frameworks have generally been considered purely in terms of competence. The idea of capability introduces approaches that make them more able to respond to factors such as emergent contexts, evolving and contested practices and the need for intelligent judgement and lived ethical practice.